The Effect of K3EDTA Blood Volume Variation on Complete Blood Count Results - La Ode Marsudi; Wahid, Rifky Saldi A.; Mawardani, Maya Tamara; Rinda Aulia Utami (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of varying K3EDTA blood volumes on complete blood count (CBC) results. Venous blood collection was performed using a closed system method. Blood was collected into K3EDTA vacutainer tubes with varying volumes of 1 mL, 2 mL, and 3 mL for each respondent, with a total of 10 respondents. The CBC parameters examined were WBC, RBC, Hb, Hct, MCV, MCH, MCHC, and PLT, using a quality-controlled hematology analyzer. Normally distributed data were analyzed using ANOVA, while non-normally distributed data were analyzed using the Friedman test. The results showed p-values > 0.05 for WBC, RBC, Hb, Hct, MCV, MCH, and MCHC, whereas the PLT test results showed a p-value < 0.05. The conclusion of this study is that there is an effect of varying K3EDTA blood volumes on PLT test results, but no effect on WBC, RBC, Hb, Hct, MCV, MCH, and MCHC test results.